TRANSBOUNDARY ENVIRONMENTAL GOVERNANCE IN THE EU AND SOUTHEAST ASIA: CONTESTING HYBRIDITY IN THE BIOFUELS AND PALM OIL REGIMES - Helena Varkkey (JAS (Journal of ASEAN Studies), 2021)
The research addresses the complexities of the European Union’s Renewable Energy Directives (EU RED and RED II), contextualising them within the palm oil sector in Southeast Asia, in which Indonesia and Malaysia are known to be the two largest producers and exporters of palm oil. It aims to question the effect of this expanding role of markets on power dynamics and political processes. Examining these developments at different organisational scales highlights the asymmetrical power relations that circulate through such transboundary networks to shape patterns of resource access and the distribution of environmental risks. Employing a qualitative approach, the research uses case study method to reflect on how market forces and broad political dynamics establish the hybrid environmental governance regime of biofuels. The research concludes that this transboundary market approach to biofuels and palm oil should be regarded with caution, as it (1) lowers regulatory quality within the biofuels sustainability regime, (2) undermines the sustainable palm oil market, and (3) indirectly bolsters unsustainable practices outside the palm oil sector.